Simplify the expression.
(x + 2y - 5z) - (x - 4y + 6z)

(x + 2y - 5z) - (x - 4y + 6z) = (x + 2y - 5z) + (-x + 4y - 6z) = 6y - 11z

Question

Asked 4/26/2013 6:26:32 PM

Updated 155 days ago|2/17/2018 2:21:24 PM

1 Answer/Comment

Edited by Masamune [2/17/2018 2:21:02 PM]

Rating

3

(x + 2y - 5z) - (x - 4y + 6z)

= (x + 2y - 5z) + (-x + 4y - 6z)

= 6y - 11z

= (x + 2y - 5z) + (-x + 4y - 6z)

= 6y - 11z

Added 155 days ago|2/17/2018 2:21:24 PM

This answer has been confirmed as correct and helpful.

27,105,683

questions answered

There are no comments.